Halal Food Development in Bali: Dynamics of Muslim Beliefs, State Regulations, and Local Culture - Suaidi, Suaidi; Anjum, Rehana; Nasrudin, Muhamad; Maksum, Maksum; Dwi Astuti, Sriyati (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2025)
Bali faces challenges in implementing halal product assurance because the majority of its population is non-Muslim, and there is an increasing demand for halal tourism. This study aims to analyze the dynamics of halal food development in Bali in the context of religion, regulation, and local culture. The method is a socio-legal approach with interview techniques, observation, and legal document analysis. The findings show that the interaction between religious norms, state policies, and local culture affects the availability of halal food. The novelty of this study lies in the contextual approach to halal governance in non-Muslim majority areas. Recommendations include increasing halal literacy, supporting MSMEs, and strengthening locally-based halal supply chains.